A Dual-Band Branch-Line Coupler with Ultra-Wideband Harmonic Suppression - Xiao-Yu Zhang; Jong-Chul Lee (Journal of Electromagnetic Engineering and Science, 2023)
A dual-band branch-line coupler with ultra-wideband harmonic suppression is proposed in this paper. The conventional quarter-wavelength transmission lines are replaced with π-shaped lines to achieve a dual band. In addition, ultra-wideband harmonic suppression is obtained by the frequency-selecting coupling structure (FSCS) providing three transmission zeros. The two operating frequencies are 0.9 GHz and 2.0 GHz, and the corresponding −10 dB bandwidth at 0.9 GHz and 2.0 GHz is 18.9% and 10.5%, respectively. A wide harmonic suppression band is generated from 3.7 GHz to 8.3 GHz. The simulation and measurement results are in good agreement.